Determination of the inhibitory effect of the extracts of the Euphorbia helioscopia and the pH effect of these extracts in the growth of Gram positive and negative bacteria - Thekra Altai (College of Education for Pure Sciences, 1970)
ABSTRACT This research aim to study antibacterial activity of aqueous, alcoholic and methanolic extracts of aerial parts of Euphorbia helioscopia which belong to Euphorbiaceae family against some pathogenic bacteria. The results showed that aqueous extract was more active than alcoholic and methanolic extracts on growth of Staphylococcus aureus , Bacillus subtilis, Klebsiella pneumoniae, Escherichia coli , Pseudomonas aeruginosa and Salmonella typhi, comparing with Amoxycillin as a typical antibiotic. Methanolic extract showed no antibacterial activity against all bacteria studied except in Bacillus subtilis and Salmonella typhi. Minimum Inhibitory Concentration (MIC) and Minimum bactericidal concentration (MBC) value ranged from (25 ــ 200) mg/cm³, The antibacterial activity of the extracts are enhanced under acidic condition at pH = 2 and basic condition at pH = 10.